Minimal residual disease in plasma cell (multiple) myeloma: flow cytometric approaches - L. Yu. Grivtsova; V. V. Lunin; A. A. Semenova; V. B. Larionova; G. S. Tumyan (Онкогематология)
The minimum residual disease (MRD) for hematopoietic and lymphoid systems tumors is an important component of patient examination during therapy. The MRD detection is performed to evaluate the effect of therapy and risk stratification during chemotherapy (acute leukemia) or at the end of it (peripheral B-cell lymphomas). The main laboratory methods for MRD assessing are molecular (polymerase chain reaction) and immunological (multi-parameter flow cytometry (FC)) methods. Immunological evaluation of MRD is the standard of clinical protocols for the treatment of childhood acute lymphoblastic leukemia during induction therapy. In the case of acute leukemia in adults, MRD assessment is usually performed at the end of the consolidation course. Clinically significant and practically standardized is the immunological assessment of MRD in B-cell chronic lymphocytic leukemia.In multiple myeloma (in World Health Organization (2016) classification – plasma cell myeloma (PCM)), work is also underway to standardize protocols and unify approaches to MRD detection. With the introduction of new drugs and treatment regimens, as well as transplantation clinical outcome of patients significantly improved and MRD value is considered as a prognostic factor. To date, the use of the MRD value as a biomarker of treatment response in PCM has been approved by the US Food and Drug Administration.With the accumulation of our knowledge regarding the MRD and to establish the clinical significance of the FC in PCM, International Multiple Myeloma Study Group (IMWG) in 2011 was added the following definition to the traditional criteria of PCM complete remission: “Immunophenotypic complete remission” – the immunophenotypically absence of aberrant clonal plasma cells in the bone marrow when analyzing at least 1 million myelocaryocytes using a multiparameter FC (4 or more parameters).This article discusses the evolution of immunological approaches using a multi-parameter FC to detect MRD in patients with PCM in accordance with various existing protocols, features of the preanalytical stage and general rules for FC detection of MRD in PCM.